Identification and characterization of a novel PRR of fibrinogen-related protein in Apostichopus japonicus. Issue 82 (November 2018) - Jiang, Liting; Shao, Yina; Xing, Ronglian; Li, Chenghua; Cui, Yi; Zhang, Weiwei; Zhao, Xuelin
Abstract: Fibrinogen-related proteins (FREPs) play important roles in innate immunity by recognizing pathogen associated molecular patterns on pathogenic bacteria surfaces via conserved fibrinogen-like domain (FBG). In this paper, the full-length cDNA of Apostichopus japonicus FREP (designated as AjFREP ) was cloned combined with rapid amplification of cDNA ends (RACE) and transcriptome sequencing. The full-length cDNA of AjFREP was of 2110 bp with an open reading frame (ORF) of 1659 bp. SMART analysis revealed that the AjFREP contained a typical signal peptide of 19 amino acid residues, a FBG and two unusual epidermal growth factor-like domains (EGFs). Multiple sequence alignments suggested that FBG domain shared a remarkably high structural conservation in polypeptide binding site and Ca 2+ binding site. Tissue distribution analysis revealed that AjFREP was constitutively expressed in all examined tissues with the largest magnitude in coelomocytes, indicating AjFREP might play an important role in immune defense. The mRNA level of AjFREP in coelomocytes was sharply up-regulated by Vibrio splendidus challenge, and reached its peak expression at 48 h. Knock-down AjFREP by specific siRNA could significantly repress the coelomocyte phagocytosis rate. Meantime, the survival number of V. splendidus in the coelomic fluid was promoted. All these current results indicated that AjFREP might be involved in pathogen clearance through mediating coelomocytes phagocytosis activity. Highlights: The full-length cDNA of fibrinogen-related protein was identified in Apostichopus japonicus. AjFREP was constitutively expressed in all examined tissues with the largest magnitude in coelomocytes. Vibrio splendidus infection could be significantly unregulated the AjFREP mRNA expression. The coelomocyte phagocytosis rate was depressed after AjFREP silencing. AjFREP knock-down enhanced the survival of V. splendidus in the coelomic fluid.